Validating Personalized Skin Care Needs In The Indonesian Market And Exploring The Validity Of The Amity Skins Skin Test As Its Marketing Strategy - Ayu*, Valeria Christie; Sunitiyoso, Yos; Rahayu, Wulan Asti (Riwayat: Educational Journal of History and Humanities, 2023)
This research embarks on an exploration of the burgeoning field of personalized skin care in the Indonesian market, with a primary focus on Amity Skin. The research problems underpinning this study center on understanding the demand for skin care products, consumers awareness of personalized skin care, the factors influencing their purchasing these decisions. Grounded in an extensive background analysis, the scientific issue addresses the need for effective marketing strategies to implement personalized skin care solutions in Indonesias competitive market. The research progresses through distinct stages, beginning with the Customer Decision Journey and Jobs To Be Done frameworks, elucidating the consumer journey and motivations. The study then delves into quantitative analysis, employing Multiple Regression and Spearman Correlation Tests to identify the relationship between variables. The exploration extends to competitive analyses and New Wave Marketing Mix strategies. Throughout the research, underlying assumptions and hypotheses are scrutinized. The research assumes that awareness of personalized skin care in the target market is limited, necessitating an extensive awareness campaign, It also hypothesizes that factors such as tailored needs, better results, and expert recommendations positively influence purchasing decisions. Furthermore, the research posits that optimizing the user experience through the Skin Test AI-generator will significantly affect purchasing choices. This comprehensive study culminates in a set of business solutions that leverage influencer marketing campaigns, enhanced user experiences, and competitive pricing. These solutions, grounded in empirical analysis, are poised to revolutionize the personalized skin care landscape in Indonesia, empowering Amity Skin and industry stakeholders to navigate this dynamic market effectively.